Isolation gidazepam and its metabolites by solid-phase extraction - M. A. Savchenko (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Gidazepam as benzodiazepine derivative is drugs of abuse and is object of toxicological research. The first phases of analysis of analite is its insulating from biological objects. In a case of gidazepam such analites is its metabolites. One of insulating method which used in analytical toxicology is the method of solid-phase extraction (SPE). This method have advantage in comparison with is liquid extraction. However papers about studying of insulating efficiency gidazepam and its metabolites of SPE are absent now. Thus the purpose of the this paper is a study of applications of SPE in analytical toxicology. For work SPE columns Bond Elut Certify have been used (volume 3 mL, amount of a sorbent 130 mg), production of Agilent Technologies. The SPE protocols which studying have been optimised under these columns for extraction from blood and urine. Two procedures are developed for extraction in case of the general screening of an unknown drug, and two for screening of benzodiazepines. Showed that degree of extraction of the basic gidazepam`s metabolites compounds 92-98%, and for gidazepam 51-74%. Also it is positioned that acetonitrile in solutions for removal coextractive substance considerably depresses degree of extraction one of gidazeam`s metabolite. At the same time application of 1 М acetic acid promotes retention of gidazepam and its metabolites on a SPE column in the course of removal lipophilic impurities by organic solvents. Position of gidazepam and its metabolites in the schema of the general screening of an unknown drug in both SPE screening procedures is showed.